Sex determination in fish: Odontesthes spp. (Atherinopsidae) as experimental models - Fernandino, Juan Ignacio (2015)
The sex of the offspring is the result of a unique process leading, in a binary fate, to the development of male or female characteristics. In this context, the aim of the present work is to present atherinopsid fish as excellent models to study sex determination. Here we present two atherinopsid fish from South America; one species, Odontesthes bonariensis, has a strong temperature-dependent sex determination (TSD) and the other, Odontesthes hatchery, has a genotypic sex determination (GSD). However, the results obtained in the last years from our laboratories in both species show that the boundaries between these two sex determination mechanisms within Atherinopsidae are are not as rigid as previously thought and support the notion that TSD and GSD are the extremes of a continuum.